Family Law Reform in Tunisia (Reading the Rules of Polygamy in The Tunisian Code of Personal Status 1957) - Mufliha Wijayati (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2021)
This paper examines polygamy in the context of legislation in Muslim countries by taking the context of Tunisia. The prohibition of polygamy in Tunisia by criminalizing the perpetrators and their facilitators is the first in an Islamic State. Even though it has become a state regulation in the form of a law, this rule remains an issue of controversy that is debated. There have even been attempts to amend the regulation prohibiting polygamy. This research uses qualitative-literary research, with the primary data source being The Tunisian Code of Personal Status 1957. The results of the study show that there are two reasons put forward by Tunisia for prohibiting polygamy: first, the institution of enslaved people, and polygamy only existed during the developmental or transitional period of the people. Islam was prohibited during the next period of Islamic development; second, the absolute condition for the permissibility of polygamy is the ability to treat wives fairly, while historical facts prove only the Prophet saw. Who can be fair to his wives? Tunisia interprets the demand for justice not only on external issues but also on issues of deep love, compassion, and concern Qs. An-Nisa [4]: 29 is declared unable to be realized even though he has tried hard. However, the prohibition of polygamy does not benefit Muslims in Tunisia. What happened was just the opposite; various social problems emerged. For example, the trend of adultery, underhand marriage, divorce, and the phenomenon of the increasing number of old maids.This paper examines polygamy in the context of legislation in Muslim countries by taking the context of Tunisia. The prohibition of polygamy in Tunisia by criminalizing the perpetrators and their facilitators is the first in an Islamic State. Even though it has become a state regulation in the form of a law, this rule remains an issue of controversy that is debated. There have even been attempts to amend the regulation prohibiting polygamy. This research uses qualitative-literary research, with the primary data source being The Tunisian Code of Personal Status 1957. The results of the study show that there are two reasons put forward by Tunisia for prohibiting polygamy: first, the institution of enslaved people, and polygamy only existed during the developmental or transitional period of the people. Islam was prohibited during the next period of Islamic development; second, the absolute condition for the permissibility of polygamy is the ability to treat wives fairly, while historical facts prove only the Prophet saw. Who can be fair to his wives? Tunisia interprets the demand for justice not only on external issues but also on issues of deep love, compassion, and concern Qs. An-Nisa [4]: 29 is declared unable to be realized even though he has tried hard. However, the prohibition of polygamy does not benefit Muslims in Tunisia. What happened was just the opposite; various social problems emerged. For example, the trend of adultery, underhand marriage, divorce, and the phenomenon of the increasing number of old maids.